2013
DOI: 10.1038/cddis.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

Retinitis pigmentosa: rapid neurodegeneration is governed by slow cell death mechanisms

Abstract: For most neurodegenerative diseases the precise duration of an individual cell's death is unknown, which is an obstacle when counteractive measures are being considered. To address this, we used the rd1 mouse model for retinal neurodegeneration, characterized by phosphodiesterase-6 (PDE6) dysfunction and photoreceptor death triggered by high cyclic guanosine-mono-phosphate (cGMP) levels. Using cellular data on cGMP accumulation, cell death, and survival, we created mathematical models to simulate the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 43 publications
7
69
0
2
Order By: Relevance
“…It has been recently suggested that dying photoreceptors in retinitis pigmentosa display features and kinetics that differ from those of classical apoptosis and necrosis and that may constitute a new type of cell death. 56 In some…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently suggested that dying photoreceptors in retinitis pigmentosa display features and kinetics that differ from those of classical apoptosis and necrosis and that may constitute a new type of cell death. 56 In some…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in long term organotypic retinal explant cultures, at concentrations of up to 200 M, Zaprinast induces selective photoreceptor death without affecting other retinal neurons (37). Why does Zaprinast not cause generalized cell death and instead appears to affect only PDE6 under culture conditions (37)(38)(39)(40)? Tissue culture medium, such as R16 (41), used for organotypic retinal culture contains both fatty acids and glutamine.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 99%
“…High oxygen levels are toxic to photoreceptors, since they result in an excess of reactive oxygen species, which cause damage to lipids, proteins and DNA (Shen et al, 2005). Studies using human epithelial cells (Wang et al, 2003) and rd1 mouse photoreceptors (Sahaboglu et al, 2013) show that cells take about 72 hours to die from hyperoxia. This corresponds to a timescale of decades for degeneration to spread across the retina (given that approximately 4000 photoreceptors lie along any direct path traced through the retina between the ora serrata and the fovea and assuming sequential cell death), a timescale consistent with degeneration in humans (Hartong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%